HUBUNGAN PERSEPSI KETIDAKCUKUPAN DAN PROMOSI SUSU FORMULA DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI UPT PUSKESMAS PAYA LOMBANG - Rini Siregar; Rini Karmila; Aminah Aminah; Sumiati Sumiati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Exclusive breastfeeding is Mother's Milk (ASI) given to children from birth to 6 months without touching food or drink, unless there are other indications. according to research [1] Exclusive breastfeeding is breast milk that is given to babies from birth until the baby is 6 months old, without the addition of drinks such as formula milk and other drinks or foods. The purpose of this study was to determine the relationship between perceptions of inadequacy and promotion of formula milk in the success of exclusive breastfeeding. This study uses a quantitative research method with a cross sectional approach, which was conducted in the area of UPT Puskesmas Paya Lombang. All mothers who have children aged 0-6 months (as many as 40 people) are the sample to be studied. The sampling technique used is total sampling from all respondents by collecting all data using a questionnaire instrument. After researching and reviewing all respondents, it can be assessed from the exposure to formula milk promotion by 80%, and the perception of insufficiency (breast milk does not come out) by 42.5%. So the results of this study the researchers gave advice to the health workers of UPT Puskesmas Paya Lombang to provide education and improve health promotion to mothers, husbands, families and communities regarding the importance of exclusive breastfeeding from antenatal care to postnatal care.